CGIAR Initiative on Agroecology - Quintero, Marcela; Wiederkehr Guerra, Gabriela Patricia; Staiger Rivas, Simone; Dickens, Chris (CGIAR System Organization, 2023)
Agroecology is a transdisciplinary, participatory, and action-oriented approach aimed at enhancing food system resilience, equity, and sustainability. It forms part of CGIAR’s 2022-2024 Research Portfolio, delivering science and innovation to transform food, land, and water systems in a climate crisis.